Circulating endothelin-1 concentrations in patients with chronic hypoxia. Issue 6 (June 1995) - Ferri, C; Bellini, C; De Angelis, C; De Siati, L; Perrone, A; Properzi, G; Santucci, A
Abstract : AIMS–To evaluate the behavior of plasma endothelin-1 in patients with chronic hypoxia. METHODS–Fifteen male patients (mean age 52.1 +/- 3.1 years) with mild chronic obstructive pulmonary disease (COPD) were studied. Twelve healthy men (mean age 48.3 +/- 5.4 years) served as controls. Both patients and controls underwent standard pulmonary function tests, echocardiographic evaluation, and arterial blood gas evaluation. Blood samples for endothelin-1 assay were taken from a previously incannulated antecubital vein after 60 minutes of rest in the supine position. Endothelin-1 was measured by radioimmunoassay after extraction from plasma. RESULTS–Patients with chronic hypoxia had lower PaO2 values (66.1 +/- 6.2 mmHg) than controls (83.8 +/- 2.7 mmHg) but PaCO2 values were similar (38.1 +/- 2.5 v 36.7 +/- 3.1 mmHg, respectively). Arterial pulmonary pressure, therefore, was higher in patients (18.1 +/- 3.7 mmHg) than in controls (10.4 +/- 2.7 mmHg) as were circulating endothelin-1 concentrations (1.22 +/- 0.36 v 0.57 +/- 0.1 pg/ml). Furthermore, plasma endothelin-1 concentrations were negatively correlated with PaO2 and directly correlated with pulmonary pressure levels. No significant correlations were found in controls. CONCLUSIONS–These results show a clear relation between chronic hypoxia and circulating endothelin-1 concentrations. Therefore, chronic hypoxia may be regarded as an important stimulus for endothelin-1 release and as one of the main contributors to increased vasoconstriction in the vascular pulmonary bed which often accompanies lung disease.